2015
DOI: 10.1094/phyto-02-15-0046-r
|View full text |Cite
|
Sign up to set email alerts
|

Testing Taxonomic Predictivity of Foliar and Tuber Resistance to Phytophthora infestans in Wild Relatives of Potato

Abstract: Potato late blight, caused by the oomycete phytopathogen Phytophthora infestans, is a devastating disease found in potato-growing regions worldwide. Long-term management strategies to control late blight include the incorporation of host resistance to predominant strains. However, due to rapid genetic changes within pathogen populations, rapid and recurring identification and integration of novel host resistance traits is necessary. Wild relatives of potato offer a rich source of desirable traits, including la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…The mosaic-like structure of our results indicates that these resistances are likely caused by a multitude of factors. These findings are in line with several inter-species studies in wild potato, where no correlation could be found between geographical location of the species and resistance against P. infestans (Khiutti et al, 2015) or A. solani (Jansky, Simon & Spooner, 2008). To further unravel the combination of factors contributing to local variations, new sampling excursions would be required, that not just collect plant and pathogen, but also measure local geographic and climatic parameters.…”
Section: Discussionsupporting
confidence: 90%
“…The mosaic-like structure of our results indicates that these resistances are likely caused by a multitude of factors. These findings are in line with several inter-species studies in wild potato, where no correlation could be found between geographical location of the species and resistance against P. infestans (Khiutti et al, 2015) or A. solani (Jansky, Simon & Spooner, 2008). To further unravel the combination of factors contributing to local variations, new sampling excursions would be required, that not just collect plant and pathogen, but also measure local geographic and climatic parameters.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with several inter-species studies in wild potato, where no correlation could be found between geographical location of the species and resistance against P. infestans (Khiutti et al, 2015) or A. solani (Jansky, Simon & Spooner, 2008).…”
Section: Manuscript To Be Reviewedsupporting
confidence: 91%
“…Potato Genebank, for example, maintains 167 accessions of S. chacoense. To address this challenge, a series of studies was carried out to determine whether taxonomic or biogeographic data could be used to predict the distribution of disease and pest resistance phenotypes in wild relatives of potato [119][120][121][122][123][124][125]. These studies were designed to test prediction at the section and species level without prior knowledge of phenotypes.…”
Section: Identifying Valuable Germplasmmentioning
confidence: 99%